Development the direction of the research of psychological components of happiness (The Journal of Psychology and Sociology, 2012)
Recently the problem of eudemonia finds more systematic forms of response to the question of what must psycholo- gists believe about happiness and well-being. Today being limited in a description of eudemonia only as a psychological well-being or just a happy emotional state is objectively seen insufficient. In general eudemonia is studied within the framework of positive psychology - a young course, which was proclaimed as an academic trend by Seligman Martin  E.P. However, the existing eudemonic concepts, decrypted through the variety of psychological components, are still on the way of becoming, comparisons with each other, and approval. We also emphasize the high importance of the problem of eudemonia in psychology right now, at a turning point, when positive psychology has formed a new idea of eudemonia def- inition – the median between the psychological well-being and the emotional state of happiness, which is called «flourish».
Keywords: happiness; the components of happiness; happiness formula; psychological well-being; subjective well- Being; PERMA; M.Seligman; questionnaire K.Riff.